A asfixia do capital sobre o trabalho no espaço agrário no litoral sul da Bahia - Souza, Dayse Maria (2017)
This PhD thesis analyzes labor mobility on the southern coast of Bahia. Initially, a reading was developed on the aspects that involve the submission of work to capital through its valorization logic. The tendency of the sociometabolic reproduction of capital is to make the labor force more and more superfluous, representing one of the contradictions of the irrational and destructive logic of its development. At the same time that it presents the need to expand its productive character, it creates its own denial. It is understood that the logic of capitalist expansion, by developing its value-creating potentialities by increasing the productive capacity of the labor force, tends to decrease its variable part by employing an ever smaller amount of labor power, increasing the levels of exploitation, thus creating a necessary suffocation for true value-makers. On one hand, the necessary suffocation materializes itself in a perverse expansion of the reserve industrial army, denying the sale of the labor force for most of the workers (throughout the social hierarchy of labor's division); on the other hand, those who manage to sell their merchandise labor force, end up performing long work hours, subjected to high levels of exploitation, leading to an increase in the process of degradation of human life in a more general aspect. Linked to the crisis and to structural unemployment, the condition of the mobile character of labor gains a differentiated materiality in the forms of reproduction of capital in the 21st century. There is an intensification of the perverse forms of submission of labor to capital, followed by a precariousness and fluidity of the labor force. For example, with the suffocating tendency of capital over labor, the determinations involving labor relations in the studied reality, accompanied by the expansive character of the capital system show a spatial restructuring that restores a new logic of its reproduction in the southern coast of Bahia. In this process, we observe a greater devaluation of the labor force and an intensification of its mobile character, extending the layer of the superfluous, placing the true producers of the surplus-value towards the paths of labor uncertainty.________________________________________________________________________________________________________________________________